Aktivitas fisik dan psikologis pada pasien chronic kidney disease yang menjalani hemodialisis: A literature review - Pangaribuan, Resmi; Tarigan, Almina Rospitaria; Anggeria, Elis; Girsang, Ermi; Gea, Saharman (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Chronic kidney disease (CKD) is a condition in which kidney function gradually declines or is even lost completely. This decline in kidney function can lead to fluid and metabolic waste accumulation in the body, which, if not properly managed, can progress to end-stage kidney failure, requiring renal replacement therapy in the form of dialysis or a kidney transplant. For patients with chronic kidney disease (CKD), the presence of caregivers and family members is the most important source of support. Purpose: To determine the physical and psychological impact of CKD on patients undergoing hemodialysis. Method: This literature review utilized databases such as PubMed, Google Scholar, and Science Direct and included articles published between 2020 and 2024. Inclusion criteria included studies discussing physical activity, quality of life, and psychological aspects in CKD patients undergoing hemodialysis. Studies not available in English or Indonesian, as well as studies not relevant to the topic, were assessed in this review. The search yielded 14 articles, which were selected through keyword selection. Results: Physical activity is an important treatment and prevention measure for chronic kidney disease. The concept of